Exercise Intervention in Women with Fibromyalgia and Its Influence on Pain, Psychological Variables, and Disability: An Observational Study - María Elena González-Álvarez; Víctor Riquelme-Aguado; Giacomo Rossettini; Josué Fernández-Carnero; Jorge Hugo Villafañe (Life)
(1) Background: Fibromyalgia syndrome (FM) is a specific condition within the spectrum of musculoskeletal pain disorders, with an estimated global prevalence of 2%. Physical exercise has shown promise in modulating pain and improving physical function without the drawbacks of pharmacotherapy. This study aims to examine the effects of a 6-week telerehabilitation combined exercise program—including mobility, strength, and high-intensity exercises—on pain, psychological variables, and disability in women with fibromyalgia. (2) Methods: In this observational study involving 53 FM patients, the outcomes measured were the pressure pain threshold (PPT), the conditioned pain modulation (CPM) paradigm, levels of pain on the measurement day and the average of the last week (using NRS) the impact of the fibromyalgia (using Fibromyalgia Impact Questionnaire (FIQ), and anxiety (using the Spanish version of the State–Trait Anxiety Inventory—STAI). (3) Results: Statistically significant changes were observed in the intervention group in PPT, CPM, NRS, and FIQ. (4) Conclusions: A six-week telerehabilitation therapeutic exercise intervention consisting of two scheduled exercise sessions per week lasting approximately 45 min each is associated with reduced pain levels, enhanced pain inhibitory pathways, and a decreased impact of fibromyalgia compared to patients who do not adopt a more active lifestyle.